Sikap Siswa Guru Semasa Belajar di Institut Pendidikan Guru Berasaskan Pemikiran Al-Zarnuji: Pre-Service Teacher’s Attitude During Study at Institute of Teacher Education Based on Al-Zarnuji Thought - Wan Hamat, Wan Hasmah Laili; Hamzah, Mohd Isa (Journal Al-Muqaddimah, 2020)
Pre service teachers will be the determinants of future education of the country and it is important for teachers who are undergoing training programs to be absorbed in a positive attitude while learning. Attitudes change are very significant and need to be transformed to a better direction from time to time. Therefore, this study aims to elaborate on the right course of study into practice based on Al-Zarnuji’s thinking and also identify the current level of attitude among pre service teachers. This study uses literature review method and survey study using questionnaire to get data. The data obtained were analyzed descriptively. A total of 30 pre service teacher from the Institute of Teacher Education were randomly selected as respondents for the study. The findings show that the items always come early to class and always focus on lectures are the highest level of attitudes while the lowest attainments are recorded is the practice of reviewing the lesson as soon as the class ends). The level of attitude of the students when studying as a whole was at moderate level and showed positive attitude and behaviors as suggested by Al-Zarnuji in acquiring knowledge. The acceptance of Al-Zarnuji’s learning method as a practice among the students of the teacher should be widely disseminated and applied optimally so that the students of the born teacher are teachers who are not only knowledgeable and skilled, but are positive and wisely adapted in any change.